Colorectal serrated lesions and polyps in the Danish population: A large nationwide register-based cohort study - Andrea, Mille; Jepsen, Rikke Karlin; Klein, Mads Falk; Gögenur, Ismail; Kuhlmann, Tine Plato (Endoscopy International Open, 2023)
Background and study aims Colorectal serrated lesions and polyps (SPs) include hyperplastic polyps (HP), sessile serrated lesions-/+dysplasia (SSL/SSL-D), and traditional serrated adenomas (TSA). From 20% to 30% of colorectal cancers (CRC) develop from SP. We present incidence and baseline characteristics of SP in a Danish cohort.Patients and methods We used The Danish Pathology Registry to include all SPs in the Danish population from January 1, 2000 to December 31, 2021. Based on the unique Danish personal identification number and SNOMED-codes, combined with the age and sex of patients, and date of procedure, we determined the incidence of the SP subtypes, anatomical location, and changes over time.Results During the period from 2000 to 2021, a total of 292,761 SPs were removed from 163,840 patients: 51,649 SSLs, 5959 SSL-Ds, 224,860 HDs, and 10,293 TSAs. The median age of patients was 64.1 years (range 55.2–71.6) and 53.3% were male. We found a general increase in SPs from 3525 in 2000 to 25,853 in 2021 and a rise in the SSL proportion from 1.7% in 2006 to 38% in 2021. Half of all patients had more than one lesion at endoscopy with conventional adenomas being the most common. CRC was found along with SPs in 3.3% of procedures, while 1% to 2.5% of the patients developed metachronous CRC.Conclusions We found an increasing number of SPs, especially SSLs. From 2019 to 2021 the number of SPs seem to stabilize, while the proportion of SSLs keeps rising. Synchronous lesions were common along all subtypes of SP.
Keywords: Colorectal cancer; CRC screening; GI Pathology; Epidemiology